Effects of Predrying and Spontaneous Fermentation Treatments on Nib Acidification, Fermentation Quality, and Flavour Attributes of Ghanaian Cocoa (Theobroma cacao) Beans - Lukeman Haruna; Ernest E. Abano; Ernest Teye; Isaac Tukwarlba; Wilson Yeboah; Kesse J. Agyei; Mary Lukeman (International Journal of Food Science)
Cocoa bean acidification, fermentation, and flavour quality are intricately shaped by pulp preconditioning and fermentation treatments. This study investigates the impact of predrying and subsequent fermentation on key parameters such as pH, titratable acidity, fermentation quality (% purity), fermentation index (FI), and overall flavour quality (global quality (GQ)) of cocoa beans. Extended predrying periods and fermentation durations demonstrated a significant enhancement in bean acidification, reflected in the rise of nib pH (6.61–7.33) and the decline in nib acidity (0.023–0.013 meg NaOH/100 g). Notably, the cut test underscored the substantial improvement in % purity, reaching 75.6–99.7% for beans predried at 2–8 hours followed by a 6-day of fermentation. FI increased significantly from 1.026 to a peak of 1.067, followed by a decline to 0.098 in the control, 6 hours, and 8 hours of predried beans, respectively. Sensory evaluation showed substantial improvement in the GQ (40.1–44.6) of beans predried at 2–8 hours and fermented for 6 days, compared to the control (38.3). In addition, a significantly higher preference was shown for cocoa liquor made from the beans predried for 4-6 hours and fermented for 6 days. Principal component analysis clustered samples according to the predrying time, fermentation duration, and quality parameters measured. Optimal conditions for enhanced nib acidification, fermentation quality, and flavour attributes were identified at 6-hour predrying and 6-day fermentation using the response surface methodology. The study highlights the potential of predrying as a pulp preconditioning technique for enhancing fermentative and final bean quality.